A Visual Task Management Application for Acute Ischemic Stroke Care - Matsumoto, Shoji; Koyama, Hiroshi; Nakahara, Ichiro; Ishii, Akira; Hatano, Taketo; Ohta, Tsuyoshi; Tanaka, Koji; Ando, Mitsushige; Chihara, Hideo; Takita, Wataru; Tokunaga, Keisuke; Hashikawa, Takuro; et al. (Frontiers in Neurology, 2019)
Background: To maximize the effect of intravenous (IV) thrombolysis and/or endovascular therapy (EVT) for acute ischemic stroke (AIS), stroke centers need to establish a parallel workflow on the basis of a code stroke (CS) protocol. At Kokura Memorial Hospital (KMH), we implemented a CS system in January 2014; however, the process of information sharing within the team has occasionally been a burdensome. Objective: To solve this problem using information communication technology (ICT), we developed a novel application for smart devices, named “Task Calc. Stroke” (TCS), and aimed to investigate the impact of TCS on AIS care. Methods: TCS can visualize the real-time progress of crucial tasks for AIS on a dashboard by changing color indicators. From August 2015 to March 2017, we installed TCS at KMH and recommended its use during normal business hours (NBH). We compared the door-to-computed tomography time, the door-to-complete blood count (door-to-CBC) time, the door-to-needle for IV thrombolysis time, and the door-to-puncture for EVT time among three treatment groups, one using TCS (“TCS-based CS”), one not using TCS (“Phone-based CS”), and one not based on CS (“non-CS”). A questionnaire survey regarding communication problems was conducted among the CS teams at 3 months after the implementation of TCS. Results: During the study period, 74 patients with AIS were transported to KMH within 4.5 hours from onset during NBH, and 53 were treated using a CS approach (phone-based CS: 26, TSC-based CS: 27). The door-to-CBC time was significantly reduced in the TCS-based CS group compared to the Phone-based CS group, from 31 to 19 minutes (p = 0.043) Other processing times were also reduced, albeit not significantly. The rate of IV thrombosis was higher in the TCS-based CS group (78% vs. 46%, p = 0.037). The questionnaire was correctly filled in by 34/38 (89%) respondents, and 82% of the respondents felt a reduction in communication burden by using the TCS application. Conclusions: TCS is a novel approach that uses ICT to support information sharing in a parallel CS workflow in AIS care. It shortens the processing times of critical tasks and lessens the communication burden among team members.